2016
DOI: 10.1038/pcan.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment plasma fibrinogen as an independent prognostic indicator of prostate cancer patients treated with androgen deprivation therapy

Abstract: The pretreatment plasma fibrinogen level was associated with tumor progression and might have a significant role in the prognosis of the prostate cancer patients treated with ADT. Thus, we recommend adding fibrinogen to traditional prognostic model, which may improve its predictive accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…Similar to CRP, the plasma fibrinogen is also an acute-phase reaction protein of host response to tumor 10 , but its measurement is routinely performed. Besides, we have showed an association beween elevated plasma fibrinogen with poor clinical outcome for PCa patients 14 .…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Similar to CRP, the plasma fibrinogen is also an acute-phase reaction protein of host response to tumor 10 , but its measurement is routinely performed. Besides, we have showed an association beween elevated plasma fibrinogen with poor clinical outcome for PCa patients 14 .…”
Section: Introductionmentioning
confidence: 67%
“…Ziaran et al 25 demonstrated a significant increase of fibrinogen levels in prostate cancer patients after 12 months of androgen deprivation therapy, indicating fibrinogen may be association with tolerance of ADT. Our previous study showed an association between elevated plasma fibrinogen with poor clinical outcome for PCa patients 14 . Besides, as an acute-phase reaction protein 10 , fibrinogen level would be increased during systemic response of host to tumor.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Clinically, Fbg is a sensitive factor of the reaction of brinolytic system and hypercoagulable state. Not only that, brinogen is also considered to be an adhesion factor involved in tumor cell proliferation, angiogenesis and metastasis [34,35]. A large number of studies have shown that high levels of fasting igg in the body suggest a poor prognosis in patients with various cancers including nasopharyngeal cancer, esophageal cancer, colorectal cancer, and prostate cancer [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…4. Pretreatment plasma fibrinogen as an independent prognostic indicator of prostate cancer patients treated with androgen deprivation therapy [4]. Authors found that pretreatment plasma fibrinogen was an independent prognostic indicator for Chinese prostate cancer patients who received ADT.…”
mentioning
confidence: 98%